Sustainable and Dynamic Competitiveness towards Technological Leadership of Industry 4.0: Implications for East African Community - Ocident Bongomin; Eric Oyondi Nganyi; Mfanga Ramadhani Abswaidi; Emmanuel Hitiyise; Godias Tumusiime (Journal of Engineering)
The war to technology and economic powers has been the driver for industrialization in most developed countries. The first industrial revolution (industry 1.0) earned millions for textile mill owners, while the second industrial revolution (industry 2.0) opened the way for tycoons and captains of industry such as Henry Ford, John D. Rockefeller, and J.P. Morgan. The third industrial revolution (industry 3.0) engendered technology giants such as Apple and Microsoft and made magnates of men such as Bill Gates and Steve Jobs. Now, the race for the fourth industrial revolution (industry 4.0) is on and there is no option, and every country whether developed or developing must participate. Many countries have positively responded to industry 4.0 by developing strategic initiatives to strengthen industry 4.0 implementation. Unlocking the country’s potential to industry 4.0 has been of interest to researchers in the recent past. However, the extent to which industry 4.0 initiatives are being launched globally has never been divulged. Therefore, the present study aimed at exploring industry 4.0 initiatives through a comprehensive electronic survey of the literature to estimate the extent of their launching in different regions. Inferences were drawn from industry 4.0 initiatives in developed nations to be used as the recommendations for the East African Community. Results of the survey revealed that 117 industry 4.0 initiatives have been launched in 56 countries worldwide consisting of five regions: Europe (37%), North America (28%), Asia and Oceania (17%), Latin America and the Caribbean (10%), and Middle East and Africa (8%). The worldwide percentage was estimated as 25%. This revealed that there is a big gap existing between countries in the race for industry 4.0.